Formulation, characterization and co-delivery of curcumin-rosemary loaded niosomes to enhance antimicrobial activity against staphylococcus aureus strains - Elmira Mehdipour; Alireza Iranbakhsh; Amir Mirzaie (Nanomedicine Journal)
Objectives: Staphylococcus aureus is a common human pathogen that infects thousands of people every year. The growing resistance of this bacterium to antibiotics has increased the need for developing more effective and natural antimicrobial medications. In this study, niosomes loaded Rosmarinus officinalis (rosemary)@curcumin were synthesized, and their antimicrobial and anti-biofilm activity on clinical S. aureus strains was investigated.Materials and Methods: Rosmarinus officinalis (rosemary) extract was prepared through maceration and its compounds were identified by GC/MS. Niosomes loaded rosemary@curcumin were synthesized through thin-film hydration. Their characteristics were analyzed with dynamic light scattering (DLS)-zetasizer, scanning electron microscopy (SEM), Fourier-transform infrared spectroscopy (FTIR), and drug release test was studied using a dialysis bag. Finally, the antimicrobial and anti-biofilm activity against clinical strains of S. aureus were investigated using minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC), and crystal violet methods, respectively.Results: Formulated niosomes were spherical, averaged 442 nm in size, and had uniform particle distribution. FTIR results indicated the successful encapsulation of rosemary@curcumin inside niosomes with 94.23% encapsulation efficiency. In vitro drug release studies showed a slow-release pattern of rosemary@curcumin from niosomes. The MIC and MBC values of niosomes loaded rosemary@curcumin were between 32.5 and 62.5 µg/ml and showed higher antimicrobial activity. Also, the results of the biofilm inhibition test showed that niosomes loaded rosemary@curcumin reduced the rate of biofilm formation between 2 and 4 fold.Conclusion: Niosomes loaded rosemary@curcumin have suitable structure and surface characteristics and can successfully inhibit S. aureus growth and prevent its biofilm formation potency.